Knowledge mapping of therapeutic cancer vaccine from 2013 to 2022: A bibliometric and visual analysis - Juan Zhao; Bin Liao; Li Gong; Huiyao Yang; Sha Li; Yongsheng Li (Taylor & Francis Group, 2023)
The investigation of therapeutic cancer vaccines has been ongoing for the past century. Herein, we used VOSviewer and CiteSpace to perform the first global bibliometric analysis of the literature on therapeutic cancer vaccines from 2013 to 2022 aiming to explore the current status and potential research trends. The findings revealed a consistent upward trend in both publication counts and citations. The United States emerged as the leading contributor with the highest number of published papers. Additionally, the analysis of references and keywords indicated that therapeutic cancer vaccines have long been popular topics, whereas neoantigen vaccines, mRNA vaccines, combination strategies, and vaccine delivery systems are emerging research hotspots. This bibliometric study provides a comprehensive and important overview of the current knowledge and potential developments in therapeutic cancer vaccines from 2013 to 2022, which may serve as a valuable reference for scholars interested in further exploring this promising field.